The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/pcc.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Administration of Neuromuscular Blocking Agents in Children With Severe Traumatic Brain Injury on Acute Complication Rates and Outcomes

Abstract: Objective To evaluate the association between neuromuscular blocking agents (NMBA) and outcome, intracranial pressure (ICP) and medical complications in children with severe TBI. Design A secondary analysis of a randomized, controlled trial of therapeutic hypothermia. Setting 17 hospitals in US, Australia, and New Zealand Patients Children (< 18 y) with severe TBI. Interventions None for this secondary analysis. Measurements and Main Results Children received NMBA on the majority of days of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…A prospective study on children ventilated more than 24 h and treated with NMBA in continuous infusion reported a reduction of the thickness of diaphragmatic muscle, but the clinical impact of these data needs to be confirmed [62]. A secondary analysis of an RCT on therapeutic hypothermia showed the use of NMBA does not impact mortality and morbidity of critically ill children [63]. A recent case-control study reported an increase in the incidence of infections in patients with acute kidney insufficiency treated NMBA [64].…”
Section: Recommendationmentioning
confidence: 99%
“…A prospective study on children ventilated more than 24 h and treated with NMBA in continuous infusion reported a reduction of the thickness of diaphragmatic muscle, but the clinical impact of these data needs to be confirmed [62]. A secondary analysis of an RCT on therapeutic hypothermia showed the use of NMBA does not impact mortality and morbidity of critically ill children [63]. A recent case-control study reported an increase in the incidence of infections in patients with acute kidney insufficiency treated NMBA [64].…”
Section: Recommendationmentioning
confidence: 99%
“…Neuromuscular blockade has also been shown to decrease global oxygen consumption and energy expenditure in mechanically ventilated children. This is an important consideration in children who are shivering when undergoing targeted temperature management and is used extensively in patients with refractory elevations in ICP[ 56 , 57 ]. The use of barbiturate coma to treat acute, refractory intracranial hypertension for pediatric TBI has been shown to be effective in decreasing ICP and is included as a consideration for second-tier therapies in the most recent consensus-based Brain Trauma Foundation guidelines[ 15 , 16 , 58 ].…”
Section: Targets For Neuroprotection In the Picumentioning
confidence: 99%
“…In a study evaluating adherence to the 2003 Pediatric TBI guidelines in children with severe TBI who survived past 48 hours of admission, for every 1% increase in adherence there was a 1% decrease in the chance of a poor outcome at discharge (42). Multiple predictors of unfavorable neurologic outcome following pediatric TBI have been described, including elevated intracranial pressure and decreased cerebral perfusion pressures (37,42,101), low Glasgow Coma Scale (GCS) on admission (40,41,44,46), subarachnoid hemorrhage and abnormal basal cisterns (35,44), and cerebral edema (35,41,46) on neuroimaging. However, several randomized controlled trials in pediatric TBI investigating therapies such as hypothermia (102), decompressive craniectomy (103), or immune-enhancing diet (104), have failed to improve patient outcomes.…”
Section: Neurologic Outcomes Following Picu Carementioning
confidence: 99%